Tourists motivation and satisfaction on firefly-watching tour using importance-performance analysis - Syazlina Saib (2017)
Tourism industry has recognized the importance of fireflies as an ecotourism attraction. In particular, this research sought to understand the motivation and satisfaction of the firefly-watching tourists in order to assess the management's success in meeting the consumers' expectations. Therefore, there were three main research objectives that have been used as a guideline and presented as follows: (1) To analyse the demographic characteristics of firefly-watching tourists in Sabah, (2) To identify the key motivation and satisfaction attributes of firefly-watching tour and tourists' level of satisfaction, and (3) To identify the key features of firefly tour that important for the tourists by using Importance-Performance Analysis (IPA). The methods used in this research included site-based distribution of questionnaires to firefly-watching tour respondents on several firefly-watching sites in Sabah (Klias, Garama, Weston, Padang Teratak and Nanamun River) and in-site interviews with the firefly-watching tourists which were done by the researcher. To gain a better understanding of what factors detracted from the firefly-watching experience and to guide the management attention, the IPA and Leximancer analysis were used. Through the IPA analysis, it has determined that the features: good visibility, number of fireflies seen, proximity to fireflies, safety procedures on boats, and quality of transportation services were performing well and were the major strengths for the firefly-watching tour in Sabah. Overall, respondents were very satisfied with the firefly-watching tour (79.59%), and stated that they would recommend the tour (89%) to their friends and families. As a conclusion, this research has provided a greater understanding of tourists' motivation and satisfaction towards the firefly-watching tour in Sabah. In fact, the finqings of this research would act as baseline information and fulfil the current state of knowledge on the management of firefly-watching tour from the tourists' perspectives. Overall, the application of IPA has been proven to be useful for the management to effectively plan their resources and thus contribute more for the fireflies' conservation efforts and their surrounding natural habitat.